2021
DOI: 10.1186/s12889-020-10021-y
|View full text |Cite
|
Sign up to set email alerts
|

Does husband’s alcohol consumption increase the risk of domestic violence during the pregnancy and postpartum periods in Nepalese women?

Abstract: Background Domestic violence against women during pregnancy and the postpartum period not only violates the human rights of women but also harms on the health of both mother and child. Domestic violence is entrenching in social norms, customs and structural factors against women in Nepal. The use of alcohol also exacerbates domestic violence. The objective of this study was to determine the association between domestic violence against women and husband’s drinking behavior across the periods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…When we talk about partners age, we found that older men are more violent, while some other authors identified that violence occurred more often among young married couples and young parents [3,18]. Although in our study we did not inquiry about the timing of the first violent acts that happened during the marital life, other research indicated that is happens early, at the beginning of the union [3,17,18].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…When we talk about partners age, we found that older men are more violent, while some other authors identified that violence occurred more often among young married couples and young parents [3,18]. Although in our study we did not inquiry about the timing of the first violent acts that happened during the marital life, other research indicated that is happens early, at the beginning of the union [3,17,18].…”
Section: Discussionmentioning
confidence: 52%
“…We found that almost half of women/spouses experienced violence in the previous one year (46.2%). Other studies that also addressed alcohol dependent men and their abusive behavior, revealed that even in pregnancy or antenatal period women are not protected from violence: 27% of women who just delivered experienced violence [16], and Bhatta et all [17] found that pregnant women whose partners are alcohol-dependent are exposed to violence as twice as often than women whose partners are not alcohol-dependent. These findings suggest that alcohol dependent partners appeared to present an extremely high risk for perpetuation of violence, and a "red flag" that calls for an action to enhance women's protection and safety, by providing immediate protection and a long-term support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was conducted by Bhatta and others (2018) surveyed respondents (165 women) reported that the prevalence of domestic violence against women during the postpartum period was 20%. Domestic violence can happen to any woman, regardless of age, economic status, race, and educational background [17] .…”
Section: Impacts Related To Postpartummentioning
confidence: 99%
“…Several studies have introduced tools, instruments, or questionnaires for detecting pregnancy-related DV in Nepal [10, 12, 13]. The Abuse Assessment Screen (AAS), originally developed in the United States [14], has been validated in different countries, including Turkey, Greece, and Spain, demonstrating its effectiveness as a simple tool [15–17].…”
Section: Introductionmentioning
confidence: 99%